Pelatihan Pengolahan Pati Sagu Untuk Meningkatkan Pendapatan Keluarga di Kelurahan Klamalu Kabupaten Sorong - -, Susetyowati Sofia; Ahmad Jamil; Agilistya Rahayu; Nonce Marlisye Mundoni; Muhammad Arkan Rahmat; Miki Novita Bala; Nopahlin Toding Panginan; Maria Stephani Andini (Jurnal Pengabdian Masyarakat, 2023)
Sago plants are found in lowland forest swamps, freshwater, coastal areas. At maturity, sago reaches a height of 8 to 17 meters and some trees reach a height of 30 meters depending on the type and conditions where they grow. For the people of Sorong, sago starch is a source of carbohydrates with low sugar content and sago is a staple food because the carbohydrate content in sago is equivalent to rice. For this training activity, we need several preparations so that the activities carried out can run well and smoothly. The activity was carried out in Klamalu Village, Sorong Regency. The preparations included: room (chairs and tables), projector, banner, ID card, consumption and other equipment. In carrying out training activities for the community which were carried out in Klamalu Village by a training team from the UNAMIN Faculty of Economics. The stages carried out are observation, licensing, preparation, implementation: material, practice, practical assistance, discussion, material reinforcement, closing of the event. The implementation stage begins with the speaker delivering material regarding the potential use of sago. Followed by practice and assistance in the practice of making sago crackers which was followed by the community, especially the women of Klamalu Village who were present and accompanied by the production team. With feedback provided by participants through questions in discussion sessions from the team of presenters and reinforcement of material regarding labeling products and managing PIRT by the supervising lecturer. By conducting training activities for the community, it becomes a process of transferring knowledge and introducing the benefits of the potential of existing sago plants so that they can be processed into sago crackers and can also be marketed to help MSMEs in Klamalu Village, Sorong Regency.